Sesi Bermain Dan Diskusi Kelompok Sebagai Cara Untuk Mengatasi Kejenuhan Dalam Menjalani Rehabilitasi Narkotika - Kirye Elisye Marsaulina Sihombing; Randa Putra (Yayasan Literasi Sains Indonesia, 2022)
To undergo rehabilitation by enforcement is not going to be delightful. Boredom is often happened to drugs addicts and victims of drugs abuse who are undergoing rehabilitation process. Practitioner uses group intervention method generally by starting to intervene towards primary case residents at IPWL Bukit Doa Taman Getsemane; starting from Engagement stage to Termination stage. There are several answers from the residents regarding what makes them feel bored: boring foods, they are not liberated to meet their family members, too many rules to follow, whatever they do is considered awry, no smoking, monotone activities, etc. From the answers, practitioner can see that monotone activities are the main cause of the residents' boredom. Therefore, practitioner decided to multiply the residents' activities by adding game session and group discussion session to decrease residents' boredom. From the sessions that have been run, residents admit that they feel quite content, even though sometimes practitioner can see the residents somewhat look forced to join the session.